An experimental and analytical piezoelectric energy harvesting from a simply supported beam with moving mass. (October 2016) - Assadi, Hamed; Dehghan Hamani, Iraj; Tikani, Reza; Ziaei-Rad, Saeed
In this article, energy harvesting from a beam with traveling mass is studied. Harvesting was carried out by attaching a thin piezoelectric patch directly on the beam. A theoretical formulation was presented for the problem of energy harvesting from moving mass on a simply supported beam. To validate the results, an experimental setup was designed and fabricated to measure the beam response and voltage induced in the piezoelectric patch during the mass traveling on the beam. The results indicate that the analytical and experimental values for the beam midpoint deflection and the piezoelectric voltage are in good agreement. Finally, the effect of resistive load on the harvested power was considered and the optimum resistive load for maximizing the power was calculated.